Hand Transplantation - Risks and benefits: A Review - Maria João Brás Gouveia Lúcio (2020)
INTRODUCTION: Composite tissue allotransplantation (CTA) is the culmination of progress in transplantation, allowing the reconstruction of the hand in an amputee. It's possible to restore hand function, if patients meet the selection criteria. The aim of this work was to understand the hand transplantation approach, making known current aspects, risks and benefits. METHODS: A PubMed research was realized between October 2018 and March 2019, including terms like "Hand", "Hand transplantation", "Composite tissue allotransplantation", "Immunosuppression" and "Hand prosthetics". There were included papers between 1995 and 2018, with English language, amputee human adults, systematic reviews, clinical studies. 74 papers were full evaluated. RESULTS: There are technical aspects that influences the procedure like team coordination or surgical technique. It requires a long-life treatment, which has risks such as toxicity or infections. However, it allows the recovery of fine movements, and independence, to perform detailed tasks. The indications must be carefully considered, because some patients benefit from the use of prosthesis. CONCLUSION: CTA has become an option for amputees so, it's important to do more research, in order to determine the benefits of this procedure. It's not considered a life-saving procedure, so there's an ethical debate because of the risks.